2006
DOI: 10.1086/507277
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Multidrug-Resistant Bacteria as a Predictive Test for Subsequent Onset of Nosocomial Infection

Abstract: Carriage proved to be a risk factor for subsequent nosocomial infection. However, the carriage test was useful as a predictive tool only for patients with a positive test result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In France, isolation of resistant bacteria ranges from 30% to 40%, reaching a percentage of up to 78% of the units. (14) According to SENTRY (the Program of Antimicrobial Surveillance) results from Latin America and Brazil, the non-fermenting Gram negative rods (Acinetobacter spp. and Pseudomonas aeruginosa) multidrug-resistance, and the Enterobacteriaceae (Escherichia coli, Salmonella spp, Shigella spp and Proteus mirabilis), producers of the extended spectrum beta-lactamase (ESBL) constitute the main problem in pharmaceutical resistence in these countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In France, isolation of resistant bacteria ranges from 30% to 40%, reaching a percentage of up to 78% of the units. (14) According to SENTRY (the Program of Antimicrobial Surveillance) results from Latin America and Brazil, the non-fermenting Gram negative rods (Acinetobacter spp. and Pseudomonas aeruginosa) multidrug-resistance, and the Enterobacteriaceae (Escherichia coli, Salmonella spp, Shigella spp and Proteus mirabilis), producers of the extended spectrum beta-lactamase (ESBL) constitute the main problem in pharmaceutical resistence in these countries.…”
Section: Resultsmentioning
confidence: 99%
“…We observed high rates of resistant isolates, except the polymyxins, since the program's inception, in 1997. (14) Of the Gram-positive cocci, oxycillin resistance among staphylococci represents an important problem in Latin America and the United States. However, rates vary significantly between hospitals and countries, although the percentage of isolates of Staphylococcus aureus sensitive to oxacillin originatimg from cases of bacteremia in Brazil, in comparison to Latin America, has been approached: 68.2% and 68.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus infections [ 6 , 7 ]. Similarly, rectal carriage of multidrug-resistant Enterobacteriaceae on ICU admission has been identified as a key factor for subsequent bloodstream, lung, urinary tract, and central venous catheter infection [ 8 , 9 ]. Whilst the majority of these studies only assessed colonization and infection with the same bacterial species according to their antimicrobial susceptibility profile, a study conducted in a Spanish ICU found that among 77 patients who developed Pseudomonas aeruginosa ( P .…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated that for MDROs, colonization precedes infection, and antimicrobial use is higher among patients colonized with MDROs. 24,25 Importantly, our stratified analyses demonstrated consistent relationships between exposures and risk of antimicrobial receipt, including in the presumptively lower-risk strata: in the stratum of patients who were MDRO negative at baseline, tunneled catheter for CHD access still conferred a higher odds of antimicrobial receipt than arteriovenous access; and in the stratum of patients with arteriovenous access at baseline, MDRO positivity at baseline was associated with a higher odds of antimicrobial receipt. One likely interpretation of this finding is that the increased risk of antimicrobial receipt may be independent of MDRO status in patients with a tunneled catheter because of the significantly higher risk of infection with any pathogen among patients with tunneled catheter.…”
Section: Discussionmentioning
confidence: 52%